Variability of Scots pine (Pinus sylvestris L.) plus trees in the Middle and Upper Volga Region with the use of ISSR markers - O. V. Sheikina; E. M. Romanov (Вавиловский журнал генетики и селекции)
One of the serious issues in forest breeding is how to reduce the variability level in breeding populations of forest tree species that is a set of selected plus trees. The problem is that variability is jeopardized by the risk of losing the genetic diversity of future artificial forests, as well as emerging inbreeding depression in the seed plus trees progeny. DNA markers are an effective tool to study variability, identify features of the genetic structure and degree of plant differentiation. The research focuses on assessing the level of the genetic diversity and the degree of differentiation of plus trees of various geographic origin with the use of ISSR markers. We used six ISSR primers to study 270 plus trees grown in the Penza region, the Chuvash Republic, the Republic of Tatarstan and the Mari El Republic. The samples of plus trees under study were characterized by different levels of genetic diversity. Two hundred fifteen PCR fragments were identified for six ISSR primers in total, while the number of amplified fragments varied from 186 to 201 in different plus trees samples. The genetic variabil ity varied within the following limits: 95.7–96.9 %, polymorphic loci; 1.96–1.97, the number of alleles per locus; 1.31–1.48, the number of effective alleles per locus: finally, 0.291–0.429, Shannon’s index; 0.205–0.298, the expected heterozygosity. According to the analysis of molecular variance (AMOVA), 82 % of the variability of ISSR markers is typical for the plus tree samples, while only 18 % is variability among the compared groups of trees from different geographical zones. The dendrogram generated by UPGMA showed that the plus trees grown in the Penza region, the Chuvash Republic and the Republic of Tatarstan are similar in term of the genetic structure of plus trees, while the plus gene pool of Scots pine from the Mari El Republic stands alone. The results of the research prove that the level of genetic diversity, the structure of genetic variability, and the nature of differentiation of plus trees are consistent with those previously elicited for natural populations of Scots pine in the Middle and Upper Volga region.